1996
DOI: 10.1021/ie940452i
|View full text |Cite
|
Sign up to set email alerts
|

Honeycomb Reactor Washcoated with Mordenite Type Zeolite Catalysts for the Reduction of NOx by NH3

Abstract: A low pressure drop reactor was prepared by washcoating Cu ion-exchanged mordenite on a honeycomb. The reactor configuration including reaction conditions was experimentally optimized both for low-pressure drop and for high catalytic activity of the honeycomb reactor. Over 90% of NO conversion was achieved by both Cu ion-exchanged synthetic zeolite (CuHM) and natural zeolite (CuNZA). The pressure drops due to honeycomb reactors were low enough to meet the constraint of the pressure drop (5 in. of H2O) for its … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 21 publications
0
32
0
Order By: Relevance
“…S3). Zamadics et al [35] reported that EPR signal (g// = 2.381, A = 143 G) in hydrated Cu-SAPO-34 could be assigned to Cu 2+ located in the sixmembered-ring as a complex Cu(O F ) 3 (H 2 O) 3 . The similar EPR signals for Cu-CHA catalysts reported by others [26,37] were also suggested to be this type of species, such as g// = 2.39 with A = 111 G and g// = 2.394 with A = 131 G. Thus, this EPR signal should be due to the isolated Cu 2+ located in the six-membered-ring for hydrated What's more, the copper species distribution changed after hydrothermal aging over Cu 3.44 -SAPO-34 and Cu 5.15 -SAPO-34.…”
Section: H 2 -Tprmentioning
confidence: 99%
See 3 more Smart Citations
“…S3). Zamadics et al [35] reported that EPR signal (g// = 2.381, A = 143 G) in hydrated Cu-SAPO-34 could be assigned to Cu 2+ located in the sixmembered-ring as a complex Cu(O F ) 3 (H 2 O) 3 . The similar EPR signals for Cu-CHA catalysts reported by others [26,37] were also suggested to be this type of species, such as g// = 2.39 with A = 111 G and g// = 2.394 with A = 131 G. Thus, this EPR signal should be due to the isolated Cu 2+ located in the six-membered-ring for hydrated What's more, the copper species distribution changed after hydrothermal aging over Cu 3.44 -SAPO-34 and Cu 5.15 -SAPO-34.…”
Section: H 2 -Tprmentioning
confidence: 99%
“…Reducing NOx emissions is important for the improvement of air quality. The selective catalytic reduction of NOx by NH 3 engines [1]. Due to the unstable operating conditions of diesel engines and periodically increasing the exhaust temperature to replicate diesel particulate filter (DPF) regeneration, excellent catalysts should meet the following essential requirements: good SCR activity over a wide operating temperature window, high selectivity for N 2 , and outstanding hydrothermal stability.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Only very little of ligand A could be loaded on a SiC monolith of 3.5 g. To increase the surface area the SiC monoliths were first wash-coated with a porous silica top-layer of approximately 15 weight percent. [20,21] To this end monoliths were dipped in a colloidal silica solution in water. After the excess of liquid was removed the silica layer was casted at elevated temperature.…”
Section: Catalyst Preparationmentioning
confidence: 99%